2019
DOI: 10.1021/acs.energyfuels.9b01737
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Solubility Determination of Asphaltenes

Abstract: Due to their complex chemical structure, identification and characterization of asphaltenes remain a big challenge for researchers in the oil industry. In the current contribution, solution-state two-dimensional (2D) nuclear magnetic resonance (NMR) spectra of the asphaltenes, obtained from either heavy or light crude oil samples, provide information on the chemical structures of asphaltenes at the molecular level. Two-dimensional 1H–13C heteronuclear NMR measurements are particularly useful for differentiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…The chemical structures of asphaltene samples 1, 2, and 3 (samples 2, 4, and 5, respectively, in Ok et al) of the present study were clarified with the evidence of the correlations observed in both homo- and heteronuclear two-dimensional (2D) NMR experiments previously. It was possible to elucidate the chemical structures of these asphaltene samples in detail with various functional groups, including −CH 3 (branched or terminal), −C=O, −NH, −O–, −S–, and −N–NH.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The chemical structures of asphaltene samples 1, 2, and 3 (samples 2, 4, and 5, respectively, in Ok et al) of the present study were clarified with the evidence of the correlations observed in both homo- and heteronuclear two-dimensional (2D) NMR experiments previously. It was possible to elucidate the chemical structures of these asphaltene samples in detail with various functional groups, including −CH 3 (branched or terminal), −C=O, −NH, −O–, −S–, and −N–NH.…”
Section: Introductionsupporting
confidence: 81%
“…The definition of asphaltenes is based on insolubility and solubility in n -alkane and toluene type solvents, respectively. The molecular structural elucidation of asphaltene structures has been debated, , and the chemical structure of asphaltenes provides various functional groups for wet chemistry modification.…”
Section: Introductionmentioning
confidence: 99%
“…NMR methods [23,24] have proven to be extremely useful for defining the average molecular parameters of asphaltene fractions. Through the application of 1H-NMR [89][90][91], 13C-NMR [89,[92][93][94], distorsionless enhancement by polarization transfer (DEPT) [95,96], solid-state (SS) NMR [94,97,98], and magnetic resonance imaging (MRI) [99][100][101], the hydrocarbon skeleton could be described in much detail. Although the chemical structure of asphaltene samples depends on geographical origin and even wells in the same crude oil production region, the deduced picture of asphaltenes from these studies is that of aromatic polycyclic clusters variably substituted with alkyl chains that may be quite long (up to C 10 -C 12 ), and connected by alkyl and heteroatom bridges.…”
Section: Sequential Extractionmentioning
confidence: 99%
“…NMR has proven to be a powerful tool in the determination of asphaltene structures, as shown in the recent review by Ok and Mal . Solution- and solid-state NMR have been used to study asphaltene structure. Fergoug and Bouhadda studied structural parameters of the asphaltenes derived from the Algerian Hassi Messoud oilfield using 1 H and 13 C liquid NMR, finding that the PAH region contains seven fused aromatic rings (7FAR). Scotti et al concluded, from a liquid-state 1 H and 13 C NMR study, that the most probable number of fused aromatic rings in asphaltene PAHs is seven.…”
Section: Introductionmentioning
confidence: 99%